f(x) = 3x3 + 4x2 – 8x – 2 g(x) = 3x - 5 Find (f - g)(2). A. (f - g)(x) = 3x3 + 4x2 - 11x – 7 B. (f - g)(x) = 3x3 + 4x2 - 11x + 3 C. (f - g)(x) = 3x3 + 4x2 – 5x – 7 D. (f - g)(x) = 3x3 + 4x2 – 5x + 3

fx 3x3 4x2 8x 2 gx 3x 5 Find f g2 A f gx 3x3 4x2 11x 7 B f gx 3x3 4x2 11x 3 C f gx 3x3 4x2 5x 7 D f gx 3x3 4x2 5x 3 class=

Respuesta :

[tex]\begin{gathered} f(x)=3x^3+4x^2-8x-2 \\ g(x)=3x-5 \end{gathered}[/tex]

Therefore

[tex]\begin{gathered} (f-g)(x)=3x^3+4x^2-8x-3x-2-(-5) \\ =3x^3+4x^2-11x+3 \end{gathered}[/tex]

ACCESS MORE